The general equation of a line passing through two points (xb₁,y₁)Pxb₂,y₂) is expressed as
![\begin{gathered} y-y_1=m(x-x_1) \\ \text{where} \\ m\Rightarrow slope\text{ of the line, expr}essed\text{ as }m\text{ = }(y_2-y_1)/(x_2-x_1) \\ (x_1,y_1)\Rightarrow coordinate_{}\text{ of point P} \\ (x_2,y_2)\Rightarrow coordinate_{}\text{ of point Q} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jbwd23os7yn1eaxvhv8jqzij7gpsotd6n4.png)
Given that the coordinates of the two points are (-2, -3) and (3, -5), we have
![\begin{gathered} (x_1,y_1)\Rightarrow(-2,\text{ -3)} \\ (x_2,y_2)\Rightarrow(3,\text{ -5)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e6wxfhzzz0lk1vh8yzinppvb6sr715xv9e.png)
Step 1:
Evaluate the slope o the line.
The slope is thus evaluated as
![\begin{gathered} m\text{ = = }(y_2-y_1)/(x_2-x_1) \\ \text{ = }\frac{\text{-5-(-3)}}{3-(-2)} \\ =(-5+3)/(3+2) \\ \Rightarrow m\text{ = -}(2)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x984upapz64pw8i6h87xz4u6m6ekk9u5qs.png)
Step 2:
Substitute the values of x₁,
Thus, we have
![\begin{gathered} y-y_1=m(x-x_1) \\ x_1=-2 \\ y_1=-3 \\ m\text{ =- }(2)/(5) \\ \text{thus,} \\ y-(-3)\text{ = -}(2)/(5)(x-(-2)) \\ y+3\text{ =- }(2)/(5)(x+2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dl20hm83hqyu3v66xcmz6om07rb2ogad7t.png)
Step 3:
Make .
![\begin{gathered} y+3\text{ =- }(2)/(5)(x+2) \\ \text{Multiply both sides of the equation by 5 } \\ 5(y+3)\text{ = -2(x+2)} \\ \text{open brackets} \\ 5y\text{ + 15 =- 2x - 4} \\ \Rightarrow5y\text{ =- 2x - 4 -15} \\ 5y\text{ = -2x-1}9 \\ \text{divide both sides of the equation by the coefficient of y, which is 5.} \\ \text{thus,} \\ (5y)/(5)=\frac{-\text{2x-1}9}{5} \\ \Rightarrow y\text{ =- }(2)/(5)x\text{ - }(19)/(5) \end{gathered}]()
Hence, the equation of the line is
![y\text{ = -}(2)/(5)x\text{ - }(19)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/il31mg4szoo4dfdhq0lu36i7uvgf8o69p4.png)
y₁ and m into the general equation of the line.